HLA-C as a mediator of natural killer and T-cell activation: spectator or key player? - Blais, M; Dong, T; Rowland-Jones, S (2011)
The biochemical properties of the HLA-C antigen differ substantially from those of HLA-A and -B molecules. For this reason, HLA-C diversity and expression at the cell surface are much lower than its counterparts and in consequence HLA-C-restricted responses have been infrequently detected and described. In this review we summarise the key differences between HLA-C and other class I molecules and provide an update on natural killer and T-cell responses restricted by HLA-C. We also discuss the different clinical settings associated with HLA-C alleles which mainly consist of autoimmune disorders, cancers and chronic infections.